158k views
5 votes
Does anyone know this?

Does anyone know this?-example-1

2 Answers

5 votes
Answer: D .............
User Xander
by
5.2k points
6 votes

Answer:

B

Explanation:

Given

g(x) = 2x² - 6x - 56 ← factor out 2 from each term

= 2(x² - 3x - 28) ← factor the quadratic

Consider the factors of the constant term (- 28) which sum to give the coefficient of the x- term (- 3)

The factors are + 4 and - 7, since

4 × - 7 = - 28 and 4 - 7 = - 3 , thus

x² - 3x - 28 = (x + 4)(x - 7) , then

g(x) = 2x² - 6x - 56 = 2(x + 4)(x - 7) → B

User Jonathanberi
by
6.1k points